Keberkesanan Prinsip Isyarat Dalam Aplikasi Multimedia (Prolin3k) Terhadap Kemahiran Membaca Dan Menulis Serta Persepsi Motivasi Murid - Md Napeah, Ro’azeah (2020)
The study examines the effectiveness of signaling principle in the development of multimedia application (ProLin3K) towards the reading and writing skills and perceived motivation of Linus’s pupils. This study was built on Mayer Multimedia Learning Theory while the development of the application was based on ADDIE instructional design model. Visual signaling of arrow and graying out were applied to its development based on Gagne’s Nine Events of Instruction.